High fetal hemoglobin level is associated with increased risk of cerebral vasculopathy in children with sickle cell disease in Mayotte - Abdourahim Chamouine; Thoueiba Saandi; Mathias Muszlak; Juliette Larmaraud; Laurent Lambrecht; Jean Poisson; Julien Balicchi; Serge Pissard; Narcisse Elenga (BMC, 2020)
Abstract Background Understanding the genetics underlying the heritable subphenotypes of sickle cell anemia, specific to each population, would be prognostically useful and could inform personalized therapeutics.The objective of this study was to describe the genetic modulators of sickle cell disease in a cohort of pediatric patients followed up in Mayotte. Methods This retrospective cohort study analyzed clinical and biological data, collected between January1st2007 and December 31st2017, in children younger than 18 years. Results We included 185 children with 72% SS, 16% Sβ0-thalassemia and 12% Sβ + thalassemia. The average age was 9.5 years; 10% of patients were lost to follow up. The Bantu haplotype was associated with an increase in hospitalizations and transfusions. The alpha-thalassemic mutation was associated with a decrease of hemolysis biological parameters (anemia, reticulocytes), and a decrease of cerebral vasculopathy. The Single Nucleotide Polymorphisms BCL11A rs4671393, BCL11A rs11886868, BCL11A rs1427407 and HMIP rs9399137 were associated with the group of children with HbF > 10%. Patients with HbF > 10% presented a significant risk of early onset of cerebral vasculopathy. Conclusions The most remarkable result of our study was the association of SNPs with clinically relevant phenotypic groups. BCL11A rs4671393, BCL11A rs11886868, BCL11A rs1427407 and HMIP rs9399137 were correlated with HbF > 10%, a group that has a higher risk of cerebral vasculopathy and should be oriented towards the hemolytic sub-phenotype.